A retrospective of the Journal of Strategic Marketing from 1993 to 2019 using bibliometric analysis. (3rd April 2022) - Donthu, Naveen; Kumar, Satish; Paul, Justin; Pattnaik, Debidutta; Strong, Carolyn
ABSTRACT: This study applies bibliometrics to track the progressive evolution of the 27 years of the Journal of Strategic Marketing ( JSM ) between 1993 and 2019. From 15 articles in 1993, publications in JSM grew to comprise 736 papers, contributed by 1, 683 authors, by the end of 2019. The number of unique contributors stands at 1, 248, and the collaboration index of the journal is 1.29. Between 1993 and 2019, the JSM received a total of 11, 612 citations, indicating its academic popularity. The impact of the journal is demonstrated by the fact that 65 of its articles were cited at least 4, 225 times in Scopus. Network analysis bifurcates JSM articles into 6 bibliographic clusters: market orientation and company performance, competitive positioning and corporate success, referral and value-based marketing, ethical marketing, entrepreneurial and innovative marketing, and marketing conflicts . The study primarily informs potential authors by providing various indicators to develop their papers targeting JSM understanding and evolving areas for publishing their future research in the journal.